ANALISIS DINAMIS SISTEM STRUKTUR DENGAN SKEMA MASSA KONSISTEN - Hariandja, Binsar (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2015)
The paper deals with frequency analysis of irreguler framed structures. The analysis used finite element method cast in matrix formulation. Apart from frequency analysis of framed structures that assumed to be of frame with relative rigid floor system, and the mass of structure is lumped at each floor, the analysis adopted consistent mass formulation. To reduce structural degrees of freedom, static condensation and multi-point constraint algorithms where used. The natural frequency resulted out of proposed analysis was then compared to that obtained by assuming rigid floor. The difference was due to the different schemes used in the consideration of inertial mass forces.Key Words: dynamic analysis, finite element method, multi-point constraints, static condensation, natural frequency.